Benthic harpacticoids as a food source for fish. - Alheit, J. & W. Scheibel (Marine Biology, Berlin, 1982)
The trophic relationships between meiobenthic harpacticoids and juvenile predatory fish were investigated in a shallow lagoon on Bermuda. Harpacticoids represent an essential food source for the juveniles of several demersal fish species. Juveniles up to 3 cm length of one fish species feed exclusively on harpacticoids. Meiobenthic harpacticoids are therefore an important component of food chains leading to higher trophic levels. However, the feeding pressure exerted by the fish on the harpacticoid populations is negligible.